Dietary Intake of Carotenoids and Their Antioxidant and Anti-Inflammatory Effects in Cardiovascular Care - Marco Matteo Ciccone; Francesca Cortese; Michele Gesualdo; Santa Carbonara; Annapaola Zito; Gabriella Ricci; Francesca De Pascalis; Pietro Scicchitano; Graziano Riccioni (Mediators of Inflammation)
Cardiovascular disease related to atherosclerosis represents nowadays the largest cause of morbidity and mortality in developed countries. Due to inflammatory nature of atherosclerosis, several studies had been conducted in order to search for substances with anti-inflammatory activity on arterial walls, able to exert beneficial roles on health. Researches investigated the role of dietary carotenoids supplementation on cardiovascular disease, due to their free radicals scavenger properties and their skills in improving low-density lipoprotein cholesterol resistance to oxidation. Nevertheless, literature data are conflicting: although some studies found a positive relationship between carotenoids supplementation and cardiovascular risk reduction, others did not find any positive effects or even prooxidant actions. This paper aimed at defining the role of carotenoids supplementation on cardiovascular risk profile by reviewing literature data, paying attention to those carotenoids more present in our diet (β-carotene, α-carotene, β-cryptoxanthin, lycopene, lutein, zeaxanthin, and astaxanthin).